Respuesta :
For this case we have a quadratic equation given by:
[tex]4x ^ 2 + 2x-1 = 0[/tex]
The roots are found by means of the quadratic formula below:
[tex]x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2 (a)}[/tex]
Where:
[tex]a = 4\\b = 2\\c = -1[/tex]
So, we have:
[tex]x = \frac {-2 \pm \sqrt {2 ^ 2-4 (4) (- 1)}} {2 (4)}[/tex]
Or in an equivalent way we have:
[tex]x = \frac {-2 \pm \sqrt {2 ^ 2 + 4 (4) (1)}} {2 (4)}[/tex]
Answer:
The correct option will be:
[tex]x = \frac {-2 \pm \sqrt {2 ^ 2-4 (4) (- 1)}} {2 (4)}[/tex]
Answer:
a = 4, b = 2 and c= -1
Step-by-step explanation:
Quadratic formula: x =√[-b ± v(b² - 4ac)]/2a
Here quadratic equation is 4x2 + 2x – 1
a = 4, b = 2 and c= -1
x =[-b ± √(b² - 4ac)]/2a
= [-2 ± √(2² - 4*4*-1)]/2*4
= [-2 ± √(4 + 16)]/8
= [-2 ± √20)]/8
= [-2 ± 2√5)]/8
= [-1 ± √5)]/4
x = [-1 ± √5)]/4